Population genetics and diversity structure of an invasive earthworm in tropical and temperate pastures from Veracruz, Mexico - Ortíz-Gamino, Diana (Zookeys, 2020)
Pontoscolex corethrurus (Müller, 1857) is an invasive tropical earthworm, globally distributed. It reproduces through parthenogenesis, which theoretically results in low genetic diversity. The analysis of the population structure of P. corethrurus using molecular markers may significantly contribute to understanding the ecology and reproductive system of this earthworm species. This work assessed the genetic diversity and population structure of P. corethrurus with 34 polymorphic inter simple sequence repeat markers, covering four populations in tropical and temperate pastures from Veracruz State. Nuclear markers distinguished two genetic clusters, probably corresponding to two distinct genetic lineages. The number of clones detected in the AC population was lower than expected for a parthenogenetic species. Also, the apparent lack of differences in population structures related to the geographic region among the populations studied may indicate that human-mediated transference is prevalent in these areas. Still, most individuals apparently belong to lineage A, and only a few individuals seem to belong to the lineage B. Thus, the admixture signatures found among the four populations of P. corethrurus may have facilitated a successful invasion by directly increasing fitness. In summary, addressing the genetic variation of P. corethrurus with ISSR markers was a suitable approach, as it evidenced the genetic diversity and relationships in the populations evaluated.